Analysis of changes in biological parameters and stocks of coho salmon Oncorhynchus kisutch in the Bolshaya River (western Kamchatka) in 1941–2023 - O. M. Zaporozhets; G. V. Zaporozhets; A. M. Biryukov (Известия ТИНРО, 2024)
Changes in the spawning part of the Bolshaya River population of coho salmon are considered for 1941–2023. Long-term trends are revealed for the most important biological parameters of adults, in particular, decreasing in size, weight (except of late-race females), and fecundity of returning fish. The parameters for different races and sexes in different periods of time are compared statistically, with frequency analysis. Influence of duration of freshwater and marine feeding on size, weight and fecundity of coho salmon is estimated. The portion of this species in salmon catches in the Bolshaya River basin was 19 %, on average, in 1941–2023, the second after pink salmon. In 2007–2023, the catch and reproduction rate of coho salmon exceeded the average values for 1972–2002 by an order, though their registered escapement to the river decreased in 3 times. Obviously, the spawning runs were underestimated. Increasing the funding of aerial surveys on coho salmon is proposed, to make them longer and more extended and detailed. Besides, the passing of salmon to the spawning grounds can be modeled on the data of reproduction multiplicity.